Direct 3D Printing of Stretchable Circuits via Liquid Metal Co‐Extrusion Within Thermoplastic Filaments. Issue 7 (10th April 2019) - Khondoker, Mohammad A. H.; Ostashek, Adam; Sameoto, Dan
Abstract : Liquid‐metal alloys are now extensively used for stretchable electronic applications due to their superior electrical conductivity, non‐toxicity, and mechanical stability in micro‐channels. Needle‐injection and direct‐writing are the most popular techniques for patterning micro‐structured liquid metal alloys. However, embedded channels often require a very high pressure to inject liquid‐metal, and direct writing by dispensing is relatively complex due to the low viscosities and high surface tension of the metal which cause liquid to normally dispense in droplets rather than a stream. In this work, a technique to co‐axially extrude liquid‐metal alloy within an encapsulating cover fluid has been presented to obtain a continuous stable stream of liquid‐metal. Fused deposition modeling (FDM) 3D printing has been adapted to co‐extrude a liquid‐metal core with a shell made from a thermoplastic elastomer. A custom extruder system is used to directly produce conductive micro‐wires (diameter: ≈25 μm) of liquid‐metal having an insulating shell of styrene‐ethylene‐butylene‐styrene which can be stretched up to four times the original length without any noticeable mechanical and electrical loss. The system is capable of printing in‐plane conductive pathways as well as out‐of‐plane functional devices with direct‐stable encapsulation of liquid‐metal wires. This technology has been successfully used to print 2D‐pressure and 3D‐strain sensors. Abstract : A multi‐material extruder system is developed to coaxially extrude a liquid metal core with a thermoplastic elastomer shell. This technology allows direct printing of liquid metal‐based 2D pressure and 3D strain sensors. The technique is capable of producing micro‐wires with liquid metal cores of 25 μm diameter when combined with drawing steps. These micro‐wires are extremely flexible and stretchable up to 300% without substantial mechanical or electrical changes.